CRITICAL THINKING AND ITS AFFECTING FACTORS - Slameto, S (Universitas Muhammadiyah Surakarta, 2017)
The objectives of this research were to measure the success rate achieved by the alumni of Open/Distance Learning (O/DL), the Bachelor Education In-service Teachers Program (BEITP), Staya Jacana Christian University(SWCU), Salatiga in their critical thinking habit that lead to their success, and to find factors which determined their critical thinking habit. The factors concerned were student factor (learning motivation, alumniâs readiness to enter ICT community, prerequisite) or teacher factor (teacherâs ability in creating and using a new instructional context). This quantitative research belongs to the causality ex-post facto research. The data source was one class of O/ DL, the BEITP, SWCUstudents, who were chosen out of four classes, as many as 32 alumni in the academic year 2015/2016. Data were screened using a self-rating scale, which consisted of 40 items tested valid and reliable, and then reduced to 5 variablas. The BEITP, SWCU Salatiga had graduated most of its alumni who owned critical thinking habit at a high rate. The critical thinking habit was affected by the instructional contexts which enabled a new situation (Model 1), alumniâs readiness to enter the ICT community (Model 2), pre-requisite, i.e., mastery of previous lecture materials (Model 3), and studentâs learning motivation (Model 4) to reach 81%. The alumniâs critical thinking habit of 51.20% was determined by the teacherâs role in developing instructional contexts which made a new situation possible. This finding was useful for educational quality management for the effectiveness and productivity of higher education, which should have been focused on the teacher in developing an instructional strategy based on context, alumni readiness to enter the ICT community, prerequisite, and studentâs learning motivation.